Taking Up the Challenges Faced by Higher Education Institutions in Technology to Create Smart Campus - Hartati, Seri; Sumarto; Nurdin, Diding; Suryana, Asep (LPPM Undiksha, 2023)
Universities face big challenges in technology to create smart campuses to increase higher education efficiency, productivity, quality and innovation. This research aims to analyze universities' efforts to utilize technology to create smart campuses. The research uses descriptive qualitative with a phenomenological approach. Data was collected through open interviews at four universities. Research subjects include top level management, middle level management, lecturers and staff. Data analysis was performed using Bogdan & Biklen which is called data reduction, the interconnection between data and verification. The research results show that universities have made various efforts to introduce digital technology to create smart campuses. This research describes the ability of universities to realize Smart Campus in 4 levels, namely adoption, implementation, integration and optimization. However, the biggest challenge is the integration and optimization of systems used for education, research and service services. Then optimization requires policies that involve goals and targets related to integration, technological sustainability and improving the learning environment, so that it will create a smart campus.